Answer:
78
Step-by-step explanation:
40 x 76 is the equation by 4x4 of 86 and the 36
Answer:
- apple: £0.20
- banana: £0.60
Step-by-step explanation:
Let "a" and "b" represent the costs of one apple and one banana, respectively. Then the purchases can be written ...
4a +b = 1.40
7a +b = 2.00
Subtracting the first equation from the second gives ...
(7a +b) -(4a +b) = (2.00) -(1.40)
3a = 0.60 . . . . simplify
a = 0.20 . . . . . .divide by 3
Using this in the first equation, we have ...
4(0.20) +b = 1.40
b = 0.60 . . . . . subtract 0.80
The cost of an apple is £0.20; the cost of a banana is £0.60.
Answer:
(x - 8)(2x + 3)
Step-by-step explanation:
To factor a polynomial of the form
ax² + bx + c,
follow these steps:
1) Multiply ac together.
2) Find 2 factors of ac that add to b. Call these factors p and q.
3) Break up the middle term of the polynomial into px + qx.
4) Factor by grouping.
Now let's follow the steps above with your problem.
You are given the polynomial
2x² - 13x - 24,
so a = 2, b = -13, and c = -24
1) Find ac.ac is the product 2(-24) = -48
2) Now we need to find 2 factors of -48 that add to b, -13.
I know that 48 = 3 × 16, so if we use -16 and 3 for the two numbers, we have
-16 + 3 = -13
and -16 × 3 = -48.
3) Now we break up the middle term of the polynomial, -13x, into -16x + 3x.
The polynomial is now
2x² - 16x + 3x - 24
4) We factor the polynomial by grouping. To factor by grouping, you factor a common factor out of the first 2 terms and factor out a common factor out of the last two terms.
2x² - 16x + 3x - 24 =
= 2x(x - 8) + 3(x - 8)
We now see the common factor of x - 8, so we factor that out.
= (x - 8)(2x + 3)
Answer: (x - 8)(2x + 3)
You ran 6 miles on the treadmill on Monday.
Answer:
i thinks its -9
Step-by-step explanation: